Advancing the Science of Mentorship: Future Directions for Sustainable Implementation and Evaluation of Mentorship Education for the Clinical and Translational Science Workforce - Pam Asquith; Melissa McDaniels; Adriana Baez; Leonor Corsino; Roger Fillingim; Doris Rubio; Christopher Russell; Christine Sorkness; Winston Thompson; Christine Pfund (Journal of Clinical and Translational Science, 2024)
The Advancing the Science of Mentorship: Future Directions for Sustainable Implementation and Evaluation of Mentorship Education for the Clinical and Translational Science Workforce conference was held in Madison, Wisconsin, in April 2023. The conference provided an engaging and scholarly forum for clinical and translational researchers from diverse backgrounds and career stages (including leaders at Clinical and Translational Science Award (CTSA) hubs and affiliated institutions) with a professional interest and commitment to improving and diversifying workforce development and fostering a climate of inclusive excellence through best practices in mentorship. Outcomes from the conference include an online resource and a new Community of Practice.